Exploring Psychosocial Determinants of Eating Behavior: Fruit and Vegetable Intake Among Brazilian Adolescents - Moraes, César Henrique de Carvalho; Alvarenga, Marle dos Santos; Moraes, Jéssica Maria Muniz; Cyrillo, Denise Cavallini (Frontiers in Nutrition, 2021)
In most western countries children and adolescents do not eat the recommended amounts of fruits and vegetables (FV). Theoretical frameworks on social psychology of eating such as the Reason Action Approach, Social Cognitive Theory and Theory of Normal Conduct has been applied to understand how psychosocial variables can explain FV intake. However, considering those predictors is still rare on the understanding of FV intake among adolescents (particularly in Brazil) despite its importance within eating behaviour. Therefore, the current study explored important psychosocial determinants of weekly frequency of FV intake among Brazilian’s adolescents in a model testing socioeconomic status (SES) and Body Mass Index (BMI). A cross-sectional design was performed with 429 students (58% female) mean age 14.45 (SD 1.86). Key variables of theorical framework on social psychology of food were investigated using Structural Equation Modelling. The model included self-efficacy, attitudes, and social norms (with its subcomponents descriptive and injunctive) as psychosocial predictors of weekly frequency of FV intake along with SES and BMI. An instrument developed for Brazilian Portuguese was used to collect psychosocial variables as well as to verify FV reported intake. The total model explained 45.5% of weekly frequency of FV intake and self-efficacy was the only significant psychosocial determinant (λ=0.51, p=0.001). SES also showed an important effect in the model (λ=0.21, p=0.001) while for BMI no significance was observed. In conclusion, the model was adequate to understand psychosocial determinants of weekly frequency of FV intake for Brazilian adolescents with self-efficacy and SES as the major determinants of this eating behaviour.